Fostering cultural exchange and tourism promotion through The International Student Community Service Programme 2023 10th – 24th August 2023 / Mohd Faisal Abdul Wahab, Zarifah Mohd Zain and Azila Azmi - Abdul Wahab, Mohd Faisal; Mohd Zain, Zarifah; Azmi, Azila (UiTM Global @ Office of International Affairs, 2024)
The International Student Community Service Programme, held by Universitas Sumatera Utara (USU) from 10 August to 24 August 2023, demonstrates the strength of cross-cultural engagement and service-oriented efforts. Set in the picturesque Tuk Tuk Siadong Village on Samosir Island, North Sumatera, Indonesia, this two-week programme not only provides an opportunity for international students to volunteer, but it also promotes cultural immersion and tourism in the region, with a focus on the rich Batak Toba culture and the scenic beauty of Lake Toba.